2012
DOI: 10.1111/j.1447-0594.2011.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total and green vegetable intakes on glycated hemoglobin A1c and triglycerides in elderly patients with type 2 diabetes mellitus: The Japanese Elderly Intervention Trial

Abstract: Aim:Many reports have shown that vegetable intake is effective in inhibiting the onset and progression of diabetes mellitus, although the amount of vegetable intake required to be effective remains as unclear. The present study therefore aimed to clarify the relationship between the amount of vegetable intake and glycated hemoglobin A1c (HbA1c) and other metabolic parameters using male Japanese type 2 diabetic patients aged 65 years or older as subjects.Method: Participants were 417 male type 2 diabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
1
20
1
1
Order By: Relevance
“…Most vegetables have a low digestible CHO content owing to their high proportions of water and fibre, and often displace the intake of highly processed CHO and discretionary foods . Many of the included low‐CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable‐rich diet for chronic disease prevention and management …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most vegetables have a low digestible CHO content owing to their high proportions of water and fibre, and often displace the intake of highly processed CHO and discretionary foods . Many of the included low‐CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable‐rich diet for chronic disease prevention and management …”
Section: Discussionmentioning
confidence: 99%
“…71,72 Many of the included low-CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable-rich diet for chronic disease prevention and management. [73][74][75] Recommendations for the amount and type of dietary fat to consume remains a more heavily debated topic in T2D management. Traditional approaches for T2D promote low or reduced intakes of total and saturated fat while many of the low-CHO diets analysed in the present review recommended increased, high or unrestricted fat intakes.…”
Section: Ad Libitum Energy Prescriptions Included Those In Which Partmentioning
confidence: 99%
“…The results of cohort studies showed that a sufficient intake of vegetables and fruit reduced the frequency of developing diabetes [16,17], and a diet high in dietary fiber containing vegetables might improve glycemic control [18,19]. Several studies conducted with elderly Japanese participants with T2DM demonstrated that diets rich in vegetables were correlated with improved HbA1c, serum triglyceride levels [20], and life prognosis [21]. Therefore, it is important to educate Japanese T2DM patients about the health advantages of consuming vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Intakes of healthy food can prevent or alleviate chronic diseases (Boeing et al, 2012;Takahashi et al, 2012;Woodside, Young, & McKinley, 2013), especially intakes of plant-based foods, such as vegetables, fruits, grain and legumes, which are associated with the cognitive performance of older people (Nurk et al, 2010). Among plant-based foods, vegetables have apparent advantages with high fibre and low sugar contents (Slavin & Lloyd, 2012).…”
Section: Introductionmentioning
confidence: 99%